Enhancement of handoff latency reduction mechanism of Mobile Internet Protocol Version 6 (MIPv6) - Masud, M. H.; Anwar, Farhat; Bari, S.M. Sadakatul; Mahmoud, Omer M. (2012)
MIPv6 is envisioned for next generation networks to achieve ubiquitous and seamless communications for its wide address spaces and many additional features. However, MIPv6 is not widely deployed due to handoff latency and other limitations leading to packet loss and Quality of Service (QoS) degradation for real time applications such as audio and video streaming. MIPv6 handoff latency can be categorized into layer 2 (L2) and layer 3 (L3) delays that includes link layer establishment delay, movement detection delay, address configuration delay and binding update or registration delay. Movement detection delay and address configuration including Duplicate Address Detection (DAD) in layer 2 and layer 3 respectively consume the highest time of the total delay. Therefore, an optimal solution is needed to reduce the delays in both layers. In order to reduce these handoff latencies, two solutions are proposed to focus all the delays both in L2 and L3. The first solution is the fuzzy logic technique based network awareness to reduce movement detection delay especially the scanning time in layer 2 in heterogeneous networks. The second solution is parallel DAD (PDAD) to reduce address configuration time in layer 3. Both solutions benchmarked with OMNeT++ simulator show improvements over standard MIPv6 networks. The overall handoff reduced from 1300ms to 500ms applying fuzzy logic technique at L2 and PDAD mechanism in L3 that combines 60% improvements.